Padrastos : reflexões sobre o seu papel na família recomposta - Carvalho, Fernanda Reis de (2012)
Given the complexity discussion about family, we reflect on this work about the recomposed family. This family isn't new, but currently has a new structure, based on a different configuration, being the result of a divorce or conjugal separation. In these families, coexist women and men who can or cannot perform the parental function. Our proposal was to study the stepfather´s role in these families, and the relationships between the performance of this role and the mother‟s actuation. For this, we aplly questionnaires with young people of the State of Sergipe, focusing on the family structure, and interviews with mothers and stepfathers. This research is divided into three parts. In the first, we condut a teoric discussion about recomposed families, and in special about the stepfather‟s role and mother‟s actuation, besides the analysis of IBGE‟s data, and Brazilian legislation. The second discusses about methodological aspects used and the description of participants families. In the third, we classify mothers and stepfathers types founded, and the investigation of life trajectories and discourses of the daily‟s practices that lead to action of different roles. Finally, we evidence that there is a close relationship between the mother‟s role in the family, granting or restricting the stepfather‟s action.